Amazonian chemical weathering rate derived from stony meteorite finds at Meridiani Planum on Mars - Schröder, C.; Bland, Phil; Golombek, M.; Ashley, J.; Warner, N.; Grant, J. (Macmillan Publishers Limited, 2016)
© The Author(s) 2016.Spacecraft exploring Mars such as the Mars Exploration Rovers Spirit and Opportunity, as well as the Mars Science Laboratory or Curiosity rover, have accumulated evidence for wet and habitable conditions on early Mars more than 3 billion years ago. Current conditions, by contrast, are cold, extremely arid and seemingly inhospitable. To evaluate exactly how dry today's environment is, it is important to understand the ongoing current weathering processes. Here we present chemical weathering rates determined for Mars. We use the oxidation of iron in stony meteorites investigated by the Mars Exploration Rover Opportunity at Meridiani Planum. Their maximum exposure age is constrained by the formation of Victoria crater and their minimum age by erosion of the meteorites. The chemical weathering rates thus derived are ~1 to 4 orders of magnitude slower than that of similar meteorites found in Antarctica where the slowest rates are observed on Earth.